2011
DOI: 10.1164/rccm.201010-1757oc
|View full text |Cite|
|
Sign up to set email alerts
|

Lung Stress and Strain during Mechanical Ventilation

Abstract: In healthy pigs, ventilator-induced lung damage develops only when a strain greater than 1.5-2 is reached or overcome. Because of differences in intrinsic lung properties, caution is warranted in translating these findings to humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
247
4
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(270 citation statements)
references
References 23 publications
9
247
4
10
Order By: Relevance
“…However, the strain calculations based on EELV might be a useful parameter at the bedside to assess ventilator settings. The studies of Protti et al 9, 19. clearly demonstrated that tidal volume is harmful to the lungs, whereas PEEP worked protective.…”
Section: Discussionmentioning
confidence: 99%
“…However, the strain calculations based on EELV might be a useful parameter at the bedside to assess ventilator settings. The studies of Protti et al 9, 19. clearly demonstrated that tidal volume is harmful to the lungs, whereas PEEP worked protective.…”
Section: Discussionmentioning
confidence: 99%
“…The study was approved by the Institutional Review Board and conducted in accordance with international recommendations [10]. Twelve healthy female pigs weighing 22 ± 3 kg were anesthetized and mechanically ventilated (Engstrom Carestation, GE Healthcare) with PEEP 5 cm H 2 O, tidal volume 10 ml/kg and respiratory rate adjusted to maintain PCO 2 constant throughout the experiment by capnography.…”
Section: Methodsmentioning
confidence: 99%
“…Newer data generated by quantitative computed tomography suggest that alveolar overstretching tends to manifest when the V T and PEEP more than double the aerated functional residual capacity. 18,19 The resulting overstretch ruptures the matrix and may threaten to disrupt the fibrous skeleton of the lung. Rupture is especially likely when there is force amplification (stress focusing) within a heterogeneous lung 20,21 or weakened integrity of the interconnecting tissues.…”
Section: Airway Injurymentioning
confidence: 99%